THE EFFECT OF GIVING FERMENTED SAGO DRAIN IN THE RATION ON THE QUALITY OF PEKING DUCK CARCASSES - Sari, Wenny Novita; Haryadi, Hayadi; Kamal, Mustafa; Mustaqim, Mustaqim (JURNAL BIOSAINS, 2024)
Ducks are one of the sources of high-quality animal protein, receiving attention in meeting human consumption needs. However, the cultivation of Peking ducks, which have great potential as meat producers, is still carried out extensively and has not been optimal in Indonesia. This study aims to investigate the effect of fermented sago pulp in rations on the quality of carcasses and abdominal fat of Peking ducks. The research method involved the provision of fermented sago pulp in Peking duck rations, with a focus on evaluating the quality of carcasses and abdominal fat. Peking ducks. This study used an experimental method while the design used was a completely randomized design (CRD) with 4 treatments and 3 replications so that there were 12 experimental units. The results showed that the provision of fermented sago pulp in rations showed a significant impact on live weight, carcass weight, carcass percentage, and abdominal fat of Peking ducks. Based on ANOVA analysis and DMRT test, the provision of fermented sago pulp increased all of these parameters at a significance level of P <0.01. Treatment D with 100% fermented sago dregs produced the highest live weight of 1.29 kg and the highest carcass weight of 576.11 gr, significantly different from other treatments.